What have we learned from trials on antiangiogenic agents in glioblastoma?. (January 2014) - Soffietti, Riccardo; Trevisan, Elisa; Rudà, Roberta
<x xml:space="preserve">Abstract</x> Trials on recurrent glioblastoma have shown that bevacizumab alone is able to increase response rate on MRI, median and 6-month progression-free survival (PFS), and modestly overall survival, allowing an improvement of neurological function and a reduction of steroids. Any drug combination was not superior over bevacizumab alone. A synergistic effect of CCNU has been suggested when added to bevacizumab (BELOB trial), but excluded when added to cediranib (REGAL trial). Phase III trials on bevacizumab in newly diagnosed glioblastoma have shown an improvement of PFS of 3–4 months, but failed to prolong overall survival. The AVAglio trial has reported an improvement of quality of life, while the RTOG 0825 did not, and suggested a negative impact on neurocognitive functions. The GLARIUS trial, focusing on newly diagnosed glioblastoma without MGMT methylation, suggested an advantage for bevacizumab plus irinotecan. The Phase III CENTRIC trial has excluded any role for cilengitide in addiction to standard treatment in newly diagnosed glioblastoma.